A tonalitic analogue to ancient detrital zircon - Kielman, R.; Whitehouse, M.; Nemchin, Alexander; Kemp, A. (Elsevier Science BV, 2018)
A zircon population from an Archean tonalite sample from southern West Greenland has been used as a source analogue in order to test common methods and approaches applied to ancient detrital zircon populations. Measurements of U-Th-Pb, oxygen and Lu-Hf isotopes as well as rare earth element and Ti concentrations were made in these zircon crystals and, where possible, in multiple areas within a single grain. The population is dominated by oscillatory zoned cores aged 3.82 Ga with an isotopically and compositionally distinct rim that formed at 3.59 Ga. We demonstrate that multiple age components may be erroneously inferred from within these oscillatory zoned zircon cores, both from the total population and within individual grains. This has bearing on other zircon-hosted geochemical systems, as temporal correlations may be incorrectly assigned. Oxygen and Lu-Hf isotope compositions are relatively consistent through the population with only a small number of outliers. Ranges in rare earth element and Ti abundances are evident from the total population, from which apparent inverse cooling trends may be inferred. Additionally, we show that even with enhanced filtering of Ti concentrations using light rare earth element abundances, crystallisation temperatures derived from zircon grains of a single, hand sample sized rock can yield both wide and bimodal results. Since even simple, single “source rock” zircon populations may, without careful scrutiny, portray artificially complex results, particular care must be taken in the interpretation of complex ancient detrital zircon populations.